Perlindungan Hukum bagi Karyawan PT Freeport yang Terdampak: Analisis Kebijakan Pemerintah dan Implementasinya - Amanda Fauziyyah; Pratama Setiaputra Adhidarma; Cantika Khoerunnisa Alrasyid; Dwi Desi Yayi Tarina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article discusses legal protection for PT Freeport Indonesia employees affected by Termination of Employment (PHK), focusing on government policies and their implementation in. The discussion will begin with the legal basis that protects employee rights, including Law No. 13 of 2003 concerning Manpower and Government Regulation No. 35 of 2021, which regulates employment contracts, outsourcing, working hours, rest, and layoff procedures. This article will discuss employee rights after layoffs, such as compensation, severance pay, and social security. In addition, this article discusses the role of government institutions, such as the Ministry of Manpower, in ensuring that companies carry out layoff procedures in accordance with regulations. In addition, the challenges of law enforcement for employees such as limitations in dispute resolution and lack of access to information are also of concern. This article concludes with suggestions for improving legal protection for employees affected by layoffs.